A study of the impact of DIP payment reform on coronary heart disease hospitalization costs and equity - Tao, Yingying; Shen, Keyi; Chen, Yating; Li, Chengcheng; Wu, Dan; Meng, Xuehui (Frontiers in Public Health, 2025)
BackgroundTo control the growth of healthcare costs, the Chinese government introduced a diagnosis-intervention package (DIP)-based health insurance payment reform. This study evaluated the impact of the DIP policy on hospitalization costs, Length of Hospital Stay, and Out-of-Pocket Ratio for patients with coronary heart disease (CHD).MethodsHospitalization claims data from 2020 to 2023 in City S, central China, were selected and analyzed using interrupted time series (ITS), covering 264 hospitals with January 2022 as the intervention point.ResultsAfter the implementation of DIP, hospitalization costs decreased from 8.81 to 8.57 for employee health insurance (UEBMI) (p < 0.001) and from 8.18 to 7.97 for resident health insurance (URRBMI) (p < 0.001), with even greater decreases for primary and secondary hospitals. The number of days of hospitalization decreased, from 8.82 to 7.78 (p < 0.001) for UEBMI and from 8.24 to 7.46 (p < 0.001) for URRBMI, with the largest decrease in primary hospitals. As for out-of-pocket ratio, the URRBMI increased from 20.71 to 25.2% (p < 0.001), and the UEBMI decreased from 28.67 to 23.57% (p < 0.001).ConclusionThe DIP policy was effective in controlling hospitalization costs and days, especially in primary and secondary hospitals. However, the out-of-pocket ratio of URRBMI increased and UEBMI decreased, suggesting differential impact of the policy. It is recommended that policy makers pay attention to differences in health insurance types and hospital grades to optimize the fairness and effectiveness of the policy.